2022
DOI: 10.1155/2022/6657820
|View full text |Cite
|
Sign up to set email alerts
|

Serum Autoantibodies against LRDD, STC1, and FOXA1 as Biomarkers in the Detection of Ovarian Cancer

Abstract: Purpose. This study is aimed at evaluating serum autoantibodies against four tumor-associated antigens, including LRDD, STC1, FOXA1, and EDNRB, as biomarkers in the immunodiagnosis of ovarian cancer (OC). Methods. The autoantibodies against LRDD, STC1, FOXA1, and EDNRB were measured using an enzyme-linked immunosorbent assay (ELISA) in 94 OC patients and 94 normal healthy controls (NHC) in the research group. In addition, the diagnostic values of different autoantibodies were validated in another independent v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…This transcription factor was also notably activated in malignant cells. Previous studies have established FOXA1 as a serum biomarker for ovarian cancer, with overexpression evident in ovarian tumor tissue [ 55 ]. Its role in influencing the progression and prognosis of breast and prostate cancer has also been documented, suggesting a notable influence on cancer biology [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…This transcription factor was also notably activated in malignant cells. Previous studies have established FOXA1 as a serum biomarker for ovarian cancer, with overexpression evident in ovarian tumor tissue [ 55 ]. Its role in influencing the progression and prognosis of breast and prostate cancer has also been documented, suggesting a notable influence on cancer biology [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…STC1 is also secreted by multiple cell types in the tumor microenvironment, including cancer cells, cancer associated fibroblasts, macrophages and adipocytes (48,(50)(51)(52). STC1 reversely correlates with checkpoint therapy efficacy in patients with melanoma and lung cancer and is associated with poor patient survival across multiple cancer types (49,(53)(54)(55)(56)(57)(58)(59)(60). Using RNAi technology and neutralizing antibodies, we discovered that ANGPTL4 and STC1 differentially regulated cancer-associated mesothelial cell tumor-promoting functions, and that neutralization of ANGPTL4 alone or in combination with STC1 prevented metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…STC1 was found to be a biomarker in many diseases [52][53][54][55] . In this study, we found that STC1 was highly expressed in HCC and was closely correlated with poor prognosis in HCC patients.…”
Section: Discussionmentioning
confidence: 99%